New CNS depressant cardenolide glycoside from the roots of Nerium oleander - Tiwari G.; Rathour B.K.; Mishra S.K.; Sagar R. (My University, 2025)
A new central nervous system (CNS) depressant cardenolide glycoside named nerioleanderoside (1) was isolated from active n-butanol fraction of the aqueous- ethanolic (5:95 v/v) extract of the fresh dried roots of Nerium oleander. The chemical structure of nerioleanderoside was elucidated as 3β-O-(D-diginosyl)-15 β-O-(D-glucopyranosyl)-14 β -hydroxy-card-20(22)-enolide, through spectroscopic methods including IR, HRMS, NMR spectroscopy and acidic hydrolysis. One more new cardinolide glycoside (2), fully characterized stereochemically as 3 β-O-(D-diginosyl)-(1 → 4) β-(D-glucopyranosyl)-14 β-hydroxy-card-20(22)-enolide was isolated from same n-butanol fraction. The pure nerioleanderoside (1) exhibited CNS depressant activity in Swiss mice at the dose of 15 mg/kg. © 2020